Electrolyte-resistant insulating pressure-resistant wrapping tape and preparation method thereof

By adopting a multi-layer composite structure of electrolyte-resistant insulating and pressure-resistant wrapping tape, using bismaleimide modified epoxy resin, fluorinated polystyrene nano-microspheres and nanoboronitride, the problem that traditional tape cannot meet the high electrolyte resistance and insulation requirements of new energy battery cells is solved, and higher insulation performance and electrolyte resistance are achieved.

CN118374236BActive Publication Date: 2025-04-08HEYUAN KUNTENG ELECTRONIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410507536.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-25
Publication Date
2025-04-08
Estimated Expiration
2044-04-25

AI Technical Summary

Technical Problem

Traditional wrapping tape cannot meet the strict requirements of new energy battery cells for higher standards of electrolyte tolerance and electrical insulation.

Method used

The electrolyte-resistant insulating and pressure-resistant wrapping tape adopts a multi-layer composite structure, including a PET release film layer, an adhesive layer, a PET polyester film layer and a high insulating barrier layer. The high insulating barrier layer is composed of bismaleimide modified epoxy resin, fluorinated polystyrene nanomicrospheres and nanoboronitride.

Benefits of technology

It significantly improves the insulation performance and electrolyte resistance of the wrapping tape, and can maintain good performance under harsh conditions such as high temperature, high humidity and chemical erosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004810733580000081
    Figure BDA0004810733580000081
  • Figure BDA0004810733580000091
    Figure BDA0004810733580000091
Patent Text Reader

Abstract

The present application relates to the technical field of lithium battery packaging, and specifically discloses an electrolyte-resistant insulating and pressure-resistant wrapping tape and a preparation method thereof. An electrolyte-resistant insulating and pressure-resistant wrapping tape comprises, from top to bottom, a PET release film layer, an adhesive layer, a first PET polyester film layer, a high-insulation barrier layer, and a second PET polyester film layer; the high-insulation barrier layer is formed by coating a high-insulation barrier liquid, and the high-insulation barrier liquid comprises the following raw materials in parts by weight: bismaleimide-modified epoxy resin, fluorinated polystyrene nano-microspheres, nano-boron nitride, epoxy system two-component curing agent and ethyl acetate; the adhesive layer is formed by coating an adhesive liquid, and the adhesive liquid comprises the following raw materials in parts by weight: acrylate, polytetrafluoroethylene, nano-silicon dioxide, curing agent and solvent. The electrolyte-resistant insulating and pressure-resistant wrapping tape prepared in the present application has excellent electrolyte resistance and insulation properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium battery packaging, and in particular to an electrolyte-resistant insulating and pressure-resistant wrapping tape and a preparation method thereof. Background Art

[0002] The basic structure of wrapping tape relies on high-performance PET polyester film and is combined with acrylic resin adhesive, which gives the tape a series of excellent properties. It has high and low temperature resistance, acid and alkali resistance, solvent resistance, electrical insulation and other properties. It is suitable for the metal outer packaging protection and efficient insulation of today's new energy power lithium battery cells, energy storage battery cells and other types of power batteries.

[0003] Although existing tape technology can generally meet functional requirements including temperature change resistance, chemical reagent resistance and providing necessary electrical isolation, with the continuous evolution of new energy battery cell technology and the stringent requirements for higher standards of electrolyte tolerance and electrical insulation, traditional tape cannot meet the needs of new energy battery cells. Summary of the invention

[0004] In order to solve at least one of the above technical problems and achieve better electrolyte tolerance and electrical insulation of the wrapping tape, the present application provides an electrolyte-resistant insulating and pressure-resistant wrapping tape and a preparation method thereof.

[0005] On the one hand, the present application provides an electrolyte-resistant insulating and pressure-resistant wrapping tape, which includes, from top to bottom, a PET release film layer, an adhesive layer, a first PET polyester film layer, a high-insulation barrier layer, and a second PET polyester film layer;

[0006] The high-insulation barrier layer is formed by coating a high-insulation barrier liquid, and the high-insulation barrier liquid comprises the following raw materials in parts by weight: 60-70 parts of bismaleimide-modified epoxy resin, 10-20 parts of fluorinated polystyrene nanospheres, 5-10 parts of nano boron nitride, 1-3 parts of epoxy system two-component curing agent, and 50-60 parts of ethyl acetate;

[0007] The adhesive layer is formed by coating an adhesive liquid, wherein the adhesive liquid comprises the following raw materials in parts by weight: 50-65 parts of acrylate, 15-30 parts of polytetrafluoroethylene, 4-8 parts of nano silicon dioxide, 1-3 parts of a curing agent, and 40-50 parts of a solvent.

[0008] Through the above technical scheme, the present application selects a PET release film layer, an adhesive layer, a PET polyester film layer and a high insulation barrier layer to form a multi-layer composite structure, which can effectively improve the insulation performance and electrolyte resistance of the wrapping tape.

[0009] This application selects bismaleimide-modified epoxy resin, fluorinated polystyrene nano-microspheres and nano-boron nitride as the main components of high-insulation barrier liquid. The epoxy resin is modified by bismaleimide, which can significantly improve the thermal stability, high-temperature oxidation resistance and performance retention rate of the epoxy resin under long-term use; the combination of fluorinated polystyrene nano-microspheres and resin materials can effectively improve the insulation performance of the epoxy resin; nano-boron nitride has high resistivity and breakdown strength, and has extremely high thermal stability, which can effectively improve the insulation performance of the epoxy resin, and can also enhance its adaptability and service life under harsh conditions such as high temperature, high humidity, and chemical corrosion.

[0010] Preferably, the nano-boron nitride is dopamine-modified nano-boron nitride, which is prepared by the following method: dispersing the nano-boron nitride in a mixed solution of Tris buffer solution and ethanol, then adding dopamine hydrochloride, stirring and mixing for 4-5 hours, filtering, washing with water, and drying to obtain the modified nano-boron nitride; wherein the mass ratio of the nano-boron nitride to dopamine hydrochloride is (4-6):1.

[0011] Through the above technical scheme, the present application performs dopamine modification on nano boron nitride. Since the dopamine-modified boron nitride has more active groups on its surface that can form hydrogen bonds or covalent bonds with the resin, it is more evenly dispersed in the resin matrix, thereby improving the overall performance of the resin material.

[0012] Preferably, the nano-silica is nano-silica modified by a silane coupling agent, and the multi-silane coupling agent modified nano-silica is prepared by the following method: nano-silica, a silane coupling agent and anhydrous ethanol are mixed in a mass ratio of (2-4) : 1 : (95-97), mixed and stirred at 40-45°C for 25-30 minutes, filtered, washed with anhydrous ethanol, and dried to obtain the multi-silane coupling agent modified nano-silica; wherein the silane coupling agent is selected from silane coupling agent KH-560.

[0013] Through the above technical scheme, the present application uses a silane coupling agent to modify the nano-silica, which can effectively improve the surface activity and dispersibility of the nano-silica, and an organic modified layer will be formed on the surface of the silica modified by the silane coupling agent. This modified layer can block the direct penetration of solvents and ions in the electrolyte, thereby improving the electrolyte resistance of the tape.

[0014] Optionally, the bismaleimide-modified epoxy resin is prepared by the following method: 4,4-diaminodiphenylmethane is heated and melted, and then bismaleimide is added, and the mixture is stirred and mixed at 115-120° C. for 155-20 minutes, and then epoxy resin is added and stirred and mixed to obtain the bismaleimide-modified epoxy resin.

[0015] Through the above technical scheme, bismaleimide itself has excellent high temperature resistance. Modifying it into epoxy resin can significantly improve the heat resistance level of the tape, so that it can still maintain good mechanical and electrical properties in high temperature environment; bismaleimide modification can improve the dielectric properties of epoxy resin, so that the epoxy resin has lower dielectric loss and higher breakdown voltage; it also enhances the resistance of epoxy resin to chemicals and solvents, so that the tape has better electrolyte resistance.

[0016] Optionally, the mass ratio of the bismaleimide, epoxy resin and 4,4-diaminodiphenylmethane is (1-2): (3-5): (1-2).

[0017] Optionally, the fluorinated polystyrene nanospheres are prepared by the following method: styrene containing 1.5-3wt% of divinylbenzene, water and anhydrous ethanol are mixed and stirred, potassium persulfate is added, and the mixture is mixed and stirred at 70-80°C for 2-3h, and pentafluorostyrene containing 1.5-3wt% of divinylbenzene is added, and the mixture is mixed and stirred for 2-3h, followed by centrifugation, washing and drying to obtain the fluorinated polystyrene nanospheres.

[0018] Optionally, the mass ratio of styrene, potassium persulfate and pentafluorostyrene is (8-12): (0.3-0.6): (6-10).

[0019] Optionally, the mass ratio of the bismaleimide-modified epoxy resin to the fluorinated polystyrene nanospheres is (4-6):1.

[0020] Through the above technical scheme, the present application limits the usage ratio between bismaleimide-modified epoxy resin and fluorinated polystyrene nanospheres. An appropriate amount of fluorinated polystyrene nanospheres combined with bismaleimide-modified epoxy resin can effectively reduce the dielectric constant and DC conductivity of the epoxy resin, thereby enhancing the insulation performance of the tape.

[0021] Optionally, the epoxy system two-component curing agent is 2-methylimidazole and xylidine, and the mass ratio of 2-methylimidazole to xylidine is 1:(0.8-1.5).

[0022] Optionally, the acrylic acid ester is two or more of ethyl acrylate, butyl acrylate and 2-methyl methacrylate.

[0023] Optionally, the curing agent is an isocyanate curing agent; and the solvent is one or more of toluene, ethyl acetate and butanone.

[0024] In a second aspect, the present application provides a method for preparing an electrolyte-resistant insulating pressure-resistant wrapping tape, comprising the following steps:

[0025] S1, mixing acrylate, polytetrafluoroethylene, nano-silicon dioxide, a curing agent and a solvent to obtain an adhesive liquid, coating the adhesive liquid evenly on one side of a PET release film, heating and curing the film at a temperature-keeping temperature to obtain an adhesive layer;

[0026] S2, performing corona treatment on the first PET polyester film, and laminating the first PET polyester film on the side of the adhesive layer away from the PET release film;

[0027] S3, mixing bismaleimide modified epoxy resin, fluorinated polystyrene nano-microspheres, nano boron nitride, epoxy system two-component curing agent and ethyl acetate to obtain a high insulation barrier liquid, coating the high insulation barrier liquid on the side of the first PET polyester film away from the adhesive layer, heating and curing at a high temperature to obtain a high insulation barrier layer;

[0028] S4. The second PET polyester film is subjected to corona treatment and laminated to the side of the high insulation barrier layer away from the first PET polyester film to obtain the electrolyte-resistant insulating and pressure-resistant wrapping tape.

[0029] Optionally, the coating amount of the adhesive in step S1 is 30-40 g / m 2 The coating amount of the high insulation barrier liquid in step S3 is 25-35g / m 2 .

[0030] Through the above technical scheme, the wrapping tape prepared in the present application has good electrolyte resistance and insulation performance, and the preparation method is simple, which is suitable for large-scale promotion and production.

[0031] Beneficial effects of the present invention:

[0032] 1. This application uses a PET release film layer, an adhesive layer, a PET polyester film layer and a high insulation barrier layer to form a multi-layer composite structure, which can effectively improve the insulation performance and electrolyte resistance of the wrapping tape.

[0033] 2. This application uses bismaleimide-modified epoxy resin, fluorinated polystyrene nanospheres and nano boron nitride as the main components of high-insulation barrier fluid. The epoxy resin is modified by bismaleimide, which can significantly improve the thermal stability, high-temperature oxidation resistance and performance retention rate of the epoxy resin under long-term use; the combination of fluorinated polystyrene nanospheres and resin materials can effectively improve the insulation properties of the epoxy resin; nano boron nitride has high resistivity and breakdown strength, and has extremely high thermal stability, which can effectively improve the insulation properties of the epoxy resin, and can also enhance its adaptability and service life under harsh conditions such as high temperature, high humidity, and chemical corrosion.

[0034] 3. The present application modifies nano boron nitride with dopamine. The boron nitride modified with dopamine has more active groups on its surface that can form hydrogen bonds or covalent bonds with the resin, making it more evenly dispersed in the resin matrix, thereby improving the overall performance of the resin material. The present application uses a silane coupling agent to modify nano silicon dioxide, which can effectively improve the surface activity and dispersibility of nano silicon dioxide, and the surface of the silicon dioxide modified with the silane coupling agent will form an organic modified layer, which can block the direct penetration of solvents and ions in the electrolyte, thereby improving the electrolyte resistance of the tape.

[0035] 4. The wrapping tape prepared in the present application has good electrolyte resistance and insulation performance, and the preparation method is simple, which is suitable for large-scale production. DETAILED DESCRIPTION

[0036] The present application is further described in detail below in conjunction with embodiments.

[0037] The present application designs an electrolyte-resistant insulating and pressure-resistant wrapping tape, which includes, from top to bottom, a PET release film layer, an adhesive layer, a first PET polyester film layer, a high-insulation barrier layer, and a second PET polyester film layer;

[0038] The high-insulation barrier layer is formed by coating a high-insulation barrier liquid, and the high-insulation barrier liquid comprises the following raw materials in parts by weight: 60-70 parts of bismaleimide-modified epoxy resin, 10-20 parts of fluorinated polystyrene nanospheres, 5-10 parts of nano boron nitride, 1-3 parts of epoxy system two-component curing agent, and 50-60 parts of ethyl acetate;

[0039] The adhesive layer is formed by coating an adhesive liquid, wherein the adhesive liquid comprises the following raw materials in parts by weight: 50-65 parts of acrylate, 15-30 parts of polytetrafluoroethylene, 4-8 parts of nano silicon dioxide, 1-3 parts of a curing agent, and 40-50 parts of a solvent.

[0040] The present application proposes a method for preparing an electrolyte-resistant insulating pressure-resistant wrapping tape, comprising the following steps:

[0041] S1, mixing acrylate, polytetrafluoroethylene, nano-silicon dioxide, a curing agent and a solvent to obtain an adhesive liquid, coating the adhesive liquid evenly on one side of a PET release film, heating and curing the film at a temperature-keeping temperature to obtain an adhesive layer;

[0042] S2, performing corona treatment on the first PET polyester film, and laminating the first PET polyester film on the side of the adhesive layer away from the PET release film;

[0043] S3, mixing bismaleimide modified epoxy resin, fluorinated polystyrene nano-microspheres, nano boron nitride, epoxy system two-component curing agent and ethyl acetate to obtain a high insulation barrier liquid, coating the high insulation barrier liquid on the side of the first PET polyester film away from the adhesive layer, heating and curing at a high temperature to obtain a high insulation barrier layer;

[0044] S4. The second PET polyester film is subjected to corona treatment and laminated to the side of the high insulation barrier layer away from the first PET polyester film to obtain the electrolyte-resistant insulating and pressure-resistant wrapping tape. Specific embodiments

[0046] Epoxy resin: E51 epoxy resin, Jinan Jumeihui Chemical Co., Ltd.;

[0047] Bismaleimide: CAS: 13676-54-5, Chengdu Yuanda Chemical Co., Ltd.;

[0048] Nano boron nitride: Xi'an Bona Material Technology Co., Ltd., model: BN-BN-002;

[0049] Nano-silicon dioxide: Nanjing Baoket New Materials Co., Ltd., model: PST-Q02;

[0050] Polytetrafluoroethylene: CAS: 9002-84-0, Shanghai Jizhi Biochemical Technology Co., Ltd.

[0051] Preparation Example

[0052] Preparation Example 1

[0053] Preparation Example 1 Preparation of bismaleimide modified epoxy resin

[0054] 14 kg of 4,4-diaminodiphenylmethane was heated and melted, and then 16 kg of bismaleimide was added, and the mixture was stirred and mixed at 115-120° C. for 155-20 minutes, and then 40 kg of epoxy resin was added and stirred and mixed to obtain the bismaleimide-modified epoxy resin.

[0055] Preparation Example 2

[0056] Preparation Example 2 Preparation of dopamine modified nano boron nitride

[0057] 10 kg of nano boron nitride was dispersed in a mixed solution of 20 L of Tris buffer solution (10 mmol / L, pH 8.5) and 8 L of ethanol, and then 2 kg of dopamine hydrochloride was added. After stirring and mixing for 4-5 hours, the mixture was filtered, washed with water, and dried to obtain the modified nano boron nitride.

[0058] Preparation Example 3

[0059] Preparation Example 3 Preparation of Silane Coupling Agent Modified Nano-Silica

[0060] Nano-silica, a silane coupling agent and anhydrous ethanol were mixed in a mass ratio of 3:1:96, mixed and stirred at 43°C for 28 minutes, filtered, washed with anhydrous ethanol, and dried to obtain the multi-silane coupling agent modified nano-silica.

[0061] Preparation Example 4

[0062] Preparation Example 4 Preparation of polystyrene nanospheres

[0063] 10 kg of styrene containing 2.7 wt % of divinylbenzene, 10 L of water and 15 L of anhydrous ethanol were mixed and stirred, 0.4 kg of potassium persulfate was added, and the mixture was mixed and stirred at 75° C. for 3 hours, and then centrifuged, washed and dried to obtain the polystyrene nanospheres.

[0064] Preparation Example 5-7 Preparation of Fluorinated Polystyrene Nanospheres

[0065] Preparation Example 5

[0066] 8 kg of styrene containing 2.7 wt% of divinylbenzene, 8 L of water and 12 L of anhydrous ethanol were mixed and stirred, 0.3 kg of potassium persulfate was added, and the mixture was mixed and stirred at 75° C. for 2.5 h. Then 6 kg of pentafluorostyrene containing 2.7 wt% of divinylbenzene was added, and the mixture was mixed and stirred for 3 h. The mixture was centrifuged, washed and dried to obtain fluorinated polystyrene nanospheres.

[0067] Preparation Example 6

[0068] 10 kg of styrene containing 2.7 wt% of divinylbenzene, 10 L of water and 15 L of anhydrous ethanol were mixed and stirred, 0.4 kg of potassium persulfate was added, and the mixture was mixed and stirred at 75° C. for 2.5 h. Then 8 kg of pentafluorostyrene containing 2.7 wt% of divinylbenzene was added, and the mixture was mixed and stirred for 3 h. The mixture was centrifuged, washed and dried to obtain fluorinated polystyrene nanospheres.

[0069] Preparation Example 7

[0070] 12 kg of styrene containing 2.7 wt% of divinylbenzene, 12 L of water and 18 L of anhydrous ethanol were mixed and stirred, 0.6 kg of potassium persulfate was added, and the mixture was mixed and stirred at 75° C. for 2.5 h. Then 10 kg of pentafluorostyrene containing 2.7 wt% of divinylbenzene was added, and the mixture was mixed and stirred for 3 h. The mixture was centrifuged, washed and dried to obtain fluorinated polystyrene nanospheres.

[0071] Example 1

[0072] A method for preparing an electrolyte-resistant insulating pressure-resistant wrapping tape comprises the following steps:

[0073] S1, taking 58kg of acrylate, 24kg of polytetrafluoroethylene, 6kg of nano-silicon dioxide, 2kg of isocyanate curing agent and 45kg of solvent, stirring and mixing to obtain an adhesive liquid, and evenly coating the adhesive liquid on one side of the PET release film, heating and heating, and curing at the same time to obtain an adhesive layer;

[0074] The acrylate is ethyl acrylate, butyl acrylate and methyl 2-methacrylate in a mass ratio of 1:1:1, and the solvent is toluene and ethyl acetate in a mass ratio of 1:1;

[0075] S2, performing corona treatment on the first PET polyester film, and laminating the first PET polyester film on the side of the adhesive layer away from the PET release film;

[0076] S3, 65 kg of bismaleimide-modified epoxy resin of Preparation Example 1, 15 kg of fluorinated polystyrene nanospheres of Preparation Example 5, 7 kg of nano boron nitride, 2 kg of epoxy system two-component curing agent and 55 kg of ethyl acetate are stirred and mixed to obtain a high-insulation barrier liquid, and the high-insulation barrier liquid is applied to the side of the first PET polyester film away from the adhesive layer, heated and cured to obtain a high-insulation barrier layer;

[0077] The epoxy system two-component curing agent is 2-methylimidazole and dimethylbenzene in a mass ratio of 1:1;

[0078] S4. The second PET polyester film is subjected to corona treatment and laminated to the side of the high insulation barrier layer away from the first PET polyester film to obtain the electrolyte-resistant insulating and pressure-resistant wrapping tape.

[0079] The coating amount of the adhesive in step S1 is 35 g / m 2 The coating amount of the high insulation barrier liquid in step S3 is 30 g / m 2 .

[0080] Example 2

[0081] A method for preparing an electrolyte-resistant insulating pressure-resistant wrapping tape comprises the following steps:

[0082] S1, taking 50kg of acrylate, 15kg of polytetrafluoroethylene, 4kg of nano-silicon dioxide, 1kg of isocyanate curing agent and 40kg of solvent, stirring and mixing to obtain an adhesive liquid, and evenly coating the adhesive liquid on one side of the PET release film, heating and heating, and curing at the same time to obtain an adhesive layer;

[0083] Wherein, the acrylate is ethyl acrylate and butyl acrylate in a mass ratio of 1:1, and the solvent is toluene;

[0084] S2, performing corona treatment on the first PET polyester film, and laminating the first PET polyester film on the side of the adhesive layer away from the PET release film;

[0085] S3, 60 kg of the bismaleimide-modified epoxy resin of Preparation Example 1, 10 kg of the fluorinated polystyrene nanospheres of Preparation Example 5, 5 kg of nano boron nitride, 1 kg of epoxy system two-component curing agent and 50 kg of ethyl acetate are stirred and mixed to obtain a high-insulation barrier liquid, and the high-insulation barrier liquid is applied to the side of the first PET polyester film away from the adhesive layer, heated and cured to obtain a high-insulation barrier layer;

[0086] The epoxy system two-component curing agent is 2-methylimidazole and dimethylbenzene in a mass ratio of 1:0.8;

[0087] S4. The second PET polyester film is subjected to corona treatment and laminated to the side of the high insulation barrier layer away from the first PET polyester film to obtain the electrolyte-resistant insulating and pressure-resistant wrapping tape.

[0088] The coating amount of the adhesive in step S1 is 30 g / m 2 The coating amount of the high insulation barrier liquid in step S3 is 25 g / m 2 .

[0089] Example 3

[0090] A method for preparing an electrolyte-resistant insulating pressure-resistant wrapping tape comprises the following steps:

[0091] S1, taking 65kg of acrylate, 30kg of polytetrafluoroethylene, 8kg of nano-silicon dioxide, 3kg of isocyanate curing agent and 50kg of solvent, stirring and mixing to obtain an adhesive liquid, and evenly coating the adhesive liquid on one side of the PET release film, heating and heating, and curing at the same time to obtain an adhesive layer;

[0092] The acrylate is butyl acrylate and methyl 2-methacrylate in a mass ratio of 1:1, and the solvent is butanone;

[0093] S2, performing corona treatment on the first PET polyester film, and laminating the first PET polyester film on the side of the adhesive layer away from the PET release film;

[0094] S3, 70 kg of the bismaleimide-modified epoxy resin of Preparation Example 1, 20 kg of the fluorinated polystyrene nanospheres of Preparation Example 5, 10 kg of nano boron nitride, 3 kg of epoxy system two-component curing agent and 60 kg of ethyl acetate are stirred and mixed to obtain a high-insulation barrier liquid, and the high-insulation barrier liquid is applied to the side of the first PET polyester film away from the adhesive layer, heated and cured to obtain a high-insulation barrier layer;

[0095] The epoxy system two-component curing agent is 2-methylimidazole and dimethylbenzene in a mass ratio of 1:1.5;

[0096] S4, performing corona treatment on the second PET polyester film, and laminating the second PET polyester film to the side of the high insulation barrier layer away from the first PET polyester film, so as to obtain the electrolyte-resistant insulating and pressure-resistant wrapping tape.

[0097] The coating amount of the adhesive in step S1 is 40 g / m 2 The coating amount of the high insulation barrier liquid in step S3 is 35 g / m 2 .

[0098] Comparative Example 1

[0099] The difference between Comparative Example 1 and Example 1 is that an equal amount of epoxy resin is used in this comparative example to replace the bismaleimide-modified epoxy resin.

[0100] Comparative Example 2

[0101] The difference between Comparative Example 2 and Example 1 is that an equal amount of polystyrene nanospheres prepared in Preparation Example 4 is used in this comparative example to replace the fluorinated polystyrene nanospheres.

[0102] Embodiment 4-5

[0103] The difference between Example 4-5 and Example 1 is that the sources of the fluorinated polystyrene nanospheres are different. Example 4 uses the fluorinated polystyrene nanospheres prepared in Preparation Example 6, and Example 5 uses the fluorinated polystyrene nanospheres prepared in Preparation Example 7.

[0104] Embodiment 6-8

[0105] The difference between Example 6-8 and Example 4 is that the mass ratios of the bismaleimide-modified epoxy resin and the fluorinated polystyrene nanospheres are different. See Table 1 for the differences.

[0106] Table 1

[0107]

[0108] Example 9

[0109] The difference between Example 9 and Example 7 is that this example uses an equal amount of dopamine-modified nano-boron nitride prepared in Preparation Example 2 instead of nano-boron nitride.

[0110] Example 10

[0111] The difference between Example 10 and Example 9 is that in this example, an equal amount of silane coupling agent-modified nano-silica prepared in Preparation Example 3 is used instead of nano-silica.

[0112] Experimental testing

[0113] The following performance tests were performed on the wrapping tapes prepared in Examples 1-10 and Comparative Examples 1-2:

[0114] 1. Electrolyte resistance test: The tape was attached to aluminum foil and immersed in electrolyte at 80°C for 10 hours. The 180° peeling force of the tape before and after immersion was tested according to GB / T2792-2014 standard, and the retention rate of the 180° peeling force after immersion was calculated. The electrolyte was produced by Guangzhou Tianci Materials Co., Ltd.

[0115] 2. Insulation performance test: Test the insulation resistance of the tape according to IEC 61215 standard;

[0116] The tape was subjected to an aging experiment using a constant temperature and humidity aging test chamber. The damp heat aging conditions were set to 85% relative humidity, 85°C ambient temperature, and 1000h aging time. The insulation resistance of the tape was tested before and after aging, and the insulation resistance attenuation rate was calculated.

[0117] Test results

[0118] The performance test results are shown in Table 2.

[0119] Table 2

[0120]

[0121] Results Analysis

[0122] Combining Examples 1-3, Comparative Examples 1-2 and the data in Table 2, it can be seen that the wrapping tape prepared according to the present application has excellent electrolyte resistance and insulation performance, and the use of bismaleimide-modified epoxy resin and fluorinated polystyrene nanospheres can effectively improve the electrolyte resistance and insulation performance of the wrapping tape.

[0123] Combining the data of Examples 4-5, Example 1 and Table 2, it can be seen that when the mass ratio of styrene, potassium persulfate and pentafluorostyrene is (8-12): (0.3-0.6): (6-10), the prepared fluorinated polystyrene nanospheres can effectively improve the electrolyte resistance and insulation performance of the wrapping tape, and the comprehensive performance of the wrapping tape is better.

[0124] Combining the data of Examples 6-8, Example 4 and Table 2, it can be seen that when the mass ratio of bismaleimide-modified epoxy resin to fluorinated polystyrene nanospheres is (4-6):1, the comprehensive performance of the wrapping tape is better.

[0125] Combining the data of Example 9, Example 7 and Table 2, it can be seen that dopamine modification of nano-boron nitride can effectively improve its dispersibility and further enhance the electrolyte resistance and insulation performance of the wrapping tape.

[0126] Combining Example 10, Example 9 and the data in Table 2, it can be seen that modifying the nano-silicon dioxide improves the dispersibility of the nano-particles in the adhesive liquid, and further enhances the electrolyte resistance and insulation performance of the wrapping tape.

[0127] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An electrolyte-resistant insulating pressure-resistant wrapping tape, characterized in that: From top to bottom, it includes a PET release film layer, an adhesive layer, a first PET polyester film layer, a high insulation barrier layer, and a second PET polyester film layer; The high-insulation barrier layer is formed by coating a high-insulation barrier liquid, and the high-insulation barrier liquid comprises the following raw materials in parts by weight: 60-70 parts of bismaleimide-modified epoxy resin, 10-20 parts of fluorinated polystyrene nanospheres, 5-10 parts of nano boron nitride, 1-3 parts of epoxy system two-component curing agent, and 50-60 parts of ethyl acetate; The adhesive layer is formed by coating an adhesive liquid, wherein the adhesive liquid comprises the following raw materials in parts by weight: 50-65 parts of acrylate, 15-30 parts of polytetrafluoroethylene, 4-8 parts of nano silicon dioxide, 1-3 parts of a curing agent, and 40-50 parts of a solvent.

2. The electrolyte-resistant insulating pressure-resistant wrapping tape according to claim 1, characterized in that: The bismaleimide-modified epoxy resin is prepared by the following method: 4,4-diaminodiphenylmethane is heated and melted, and then bismaleimide is added, and the mixture is stirred and mixed at 115-120° C. for 155-20 minutes, and then epoxy resin is added and stirred and mixed to obtain the bismaleimide-modified epoxy resin.

3. The electrolyte-resistant insulating pressure-resistant wrapping tape according to claim 2, characterized in that: The mass ratio of the bismaleimide, epoxy resin and 4,4-diaminodiphenylmethane is (1-2): (3-5): (1-2).

4. The electrolyte-resistant insulating pressure-resistant wrapping tape according to claim 1, characterized in that: The fluorinated polystyrene nano-microspheres are prepared by the following method: styrene containing 1.5-3 wt% of divinylbenzene, water and anhydrous ethanol are mixed and stirred, potassium persulfate is added, and the mixture is mixed and stirred at 70-80°C for 2-3 hours, pentafluorostyrene containing 1.5-3 wt% of divinylbenzene is added, and the mixture is mixed and stirred for 2-3 hours, followed by centrifugation, washing and drying to obtain the fluorinated polystyrene nano-microspheres.

5. The electrolyte-resistant insulating pressure-resistant wrapping tape according to claim 4, characterized in that: The mass ratio of styrene, potassium persulfate and pentafluorostyrene is (8-12): (0.3-0.6): (6-10).

6. The electrolyte-resistant insulating pressure-resistant wrapping tape according to claim 1, characterized in that: The mass ratio of the bismaleimide modified epoxy resin to the fluorinated polystyrene nanospheres is (4-6):

1.

7. The electrolyte-resistant insulating pressure-resistant wrapping tape according to claim 1, characterized in that: The epoxy system two-component curing agent is 2-methylimidazole and xylidine, and the mass ratio of the 2-methylimidazole to xylidine is 1:(0.8-1.5).

8. The electrolyte-resistant insulating pressure-resistant wrapping tape according to claim 1, characterized in that: The acrylic acid ester is two or more selected from the group consisting of ethyl acrylate, butyl acrylate and 2-methyl methacrylate.

9. The electrolyte-resistant insulating pressure-resistant wrapping tape according to claim 1, characterized in that: The curing agent is an isocyanate curing agent; the solvent is one or more of toluene, ethyl acetate and butanone.

10. A method for preparing the electrolyte-resistant insulating pressure-resistant wrapping tape according to any one of claims 1 to 9, characterized in that: The steps include: S1, mixing acrylate, polytetrafluoroethylene, nano-silicon dioxide, a curing agent and a solvent to obtain an adhesive liquid, coating the adhesive liquid evenly on one side of a PET release film, heating and curing the film at a temperature-keeping temperature to obtain an adhesive layer; S2, performing corona treatment on the first PET polyester film, and laminating the first PET polyester film on the side of the adhesive layer away from the PET release film; S3, mixing bismaleimide modified epoxy resin, fluorinated polystyrene nanospheres, nano boron nitride, epoxy system two-component curing agent and ethyl acetate to obtain a high insulation barrier liquid, coating the high insulation barrier liquid on the side of the first PET polyester film away from the adhesive layer, heating and curing at a high temperature to obtain a high insulation barrier layer; S4, performing corona treatment on the second PET polyester film, and laminating the second PET polyester film on the side of the high insulation barrier layer away from the first PET polyester film, so as to obtain the electrolyte-resistant insulating and pressure-resistant wrapping tape.

Citation Information

Patent Citations

  • High-thermal conductivity resin composition and application thereof

    CN105623198A

  • Resin compositionc and application thereof

    CN106633646A